Identification and formation pathways of oxidation products of chlorinated paraffins during ozonation in municipal wastewater - Enrui Li; Hongping Wang; Yibin Sun; Song Tang; Chao Wang; Yi Wan; Xudong Jia; Hong Chang (Journal of Environmental Sciences, 2026)

Social media as a sensor: unraveling nonlinear drivers of perceived thermal comfort in Shanghai - Hongping Sun; Chengwei Li; Kangning Huang; Ying Li; ChengHe Guan (Landscape and Urban Planning, 2026)

Galacto-oligosaccharides enrich galactosidase-encoded rather than all Lachnospiraceae bacteria to redress abnormal gut microbiota and lipid metabolism in pregnancy - Rujun Wei; Jiyun Long; Haoxue Xia; Yanni Sun; Lin Zhang; Xiaoqing Li; Hongping Zhang; Run Wang; Shengtao Gao; Yunwei Chen; Yun Gu; Xiaoya Wang; et al. (Science China Life Sciences, 2026)

Carbon mitigation potential afforded by gridded driving forces in China - Mengqi Fan; Jian Sun; Zezhuang Liu; Yilu Gu; Shengping Li; Hongping He; Xin Liu; Xiaochen Chen; Nan Wei; Xiaofeng Gao (Journal of Environmental Sciences, 2026)

A hyper-crosslinked ionic polymer catalyzing CO2 one-pot two-step to dimethyl carbonate via HCO3-/OH- synergy - Jingya Yang; Ming Sun; Qinghua Qu; Jiquan Liang; Cheng Fang; Lei Wang; Hongping Li; Jing Ding; Hui Wan; Guofeng Guan (Journal of Environmental Chemical Engineering, 2025)

Functional differentiation of Sojae semen Praeparatum: A multi-omics analysis of the effects of Artemisia annua and Mori folium on composition, microorganisms, and functional characteristics - Yingying Cheng; Bing Wang; Qiaoling Ma; Min Sun; Xintong Wang; Ruolan Wang; Hongping Chen; Lin Chen; Youping Liu; Fu Wang; Chuan Zheng; Yuan Hu (Food Research International, 2025)

Evaluation of the particle characteristics of aggregates from construction spoils treatment through a real-time detection multimodal module based on 3D point cloud technology - Xiaohui Sun; Bowen Liao; Shuhua Huang; Minghui Liu; Silin Wu; Xiangsheng Chen; Hongping He; Hao Xiong; Zijun Dong (Waste Management, 2025)

Self-oxygenating, anti-freezing, antioxidant, and UV-resistant lignin hydrogels for wound healing at high-altitude - Chaoming Xie; Shengxi Jiang; Yingqi Li; Donglin Gan; Yingbo Wang; Hongping Zhang; Jie Weng; Zhenyu Zhang; Hongyu Sun; Xiong Lu (Chemical Engineering Journal, 2025)

Study on the Mechanism of Anti-Hail by Explosion Based on an X-Band Dual-Polarized Phased Array Radar - Liang Feng; Jiefan Yang; Hui Xiao; Yue Sun; Hongping Sun; Gang Ren; Fuxin Liu (Journal of Meteorological Research, 2025)

Detrital zircon provenance record of the northern shelf in the Rakhine Basin, Bay of Bengal - Liangbo Ding; Hongxia Ma; Guozhang Fan; Xiaoyong Xu; Hongping Wang; Guoping Zuo; Ying Zhang; Hui Sun; Jianan Wu; Junmin Jia; Ming Su; Ce Wang (Marine and Petroleum Geology, 2025)

Experimental transformation of nontronite to kaolinite: implication for ferrallitization of Fe/Mg-rich clays in compositional stratigraphy on Mars - Xiaorong Qin; Jiacheng Liu; Wei Tan; Hongping He; Joseph Michalski; Yu Sun; Shangying Li; Binlong Ye; Yiping Yang; Yiliang Li (Icarus, 2024)

A lightweight deep learning model for ocean eddy detection - Haochen Sun; Hongping Li; Ming Xu; Fan Yang; Qiang Zhao; Cuishu Li (Frontiers in Marine Science, 2023)
Ocean eddies are typical oceanic mesoscale phenomena that are numerous, widely distributed and have high energy. Traditional eddy detection methods are mainly based on physical mechanisms with high accuracy. However, the large number of steps and complex parameter settings limit their applicability for most users. With the rapid development of deep learning techniques, object detection models have been broadly used in the field of ocean remote sensing. This paper proposes a lightweight eddy detection model, ghost eddy detection YOLO (GED-YOLO), based on sea level anomaly data and the “You Only Look Once” (YOLO) series models. The proposed model used ECA+GhostNet as the backbone network and an atrous spatial pyramid pooling network as the feature enhancement network. The ghost eddy detection path aggregation network was proposed for feature fusion, which reduced the number of model parameters and improved the detection performance. The experimental results showed that GED-YOLO achieved better detection precision and smaller parameter size. Its mAP was 95.11% and the parameter size was 22.56 MB. In addition, the test experiment results showed that GED-YOLO had similar eddy detection performance and faster detection speed compared to the traditional physical method.

Microplastic Pollution and Its Potential Correlation with Environmental Factors in Daya Bay, South China Sea - Peiqin Liu; Hongping Liao; Yongyan Deng; Wenqi Zhang; Zhixi Zhou; Di Sun; Zhixin Ke; Aiguo Zhou; Huijuan Tang (Journal of Marine Science and Engineering, 2023)
Microplastics (MPs) have been given considerable attention due to their risk to aquatic organisms in marine environments. In this study, MPs’ abundance and their potential correlation with environmental factors were investigated from 26 sites in Daya Bay, South China Sea. The results showed that the abundance of MPs was 1.8–13.87 items/L in surface water and 190–823 items/kg (dry weight) in sediment. The most abundant shape of MPs in both water and sediment was fiber, the most abundant particle size was 0.5–1 mm and the most abundant color was transparent. In addition, the most common polymer type of MPs was polyethylene terephthalate (PET), followed by rayon (RY), polypropylene (PP), cellulose (CL) and polyethylene (PE). The abundance of MPs in sediment was significantly correlated with sediment organic N and C (p 0.05). A factor analysis showed that MPs in sediment might share similar sources with organic N and C, which were mainly from the autochthonous sedimentation of marine organisms, and MPs might sediment jointly with organic matter. In summary, this study reflects on MP pollution and the potential correlation with environmental factors, providing essential data for governmental agencies to formulate microplastic pollution control policies.

Mixing-layer depth-based backwards trajectory analysis of the sources of high O3 concentrations at the Wutaishan station, North China - Shiming Yan; Xingai Gao; Kunning Pei; Hongping Sun; Yan Wang; Fengsheng Zhang; Ying Li; Shumin Wang; Ling Chen; Jian Dong; Feihong Yang (Atmospheric Pollution Research, 2023)

Culture temperature modulates monoclonal antibody charge variation distribution in Chinese hamster ovary cell cultures - Xintao Zhang; Ya-Ting Sun; Hongping Tang; Li Fan; Dongdong Hu; Jintao Liu; Xuping Liu; Wen-Song Tan (Biotechnology Letters, 2015)